BREXIT AND THE IMPLICATIONS FOR TACIT CHOICE OF LAW IN THE UNITED KINGDOM - Garth Bouwers (Obiter, 2018)
The influence of European Union law on the United Kingdom is noteworthy. In the commercial arena, it has transformed the rules of private international law in the United Kingdom. The European Union has established a common framework for jurisdiction of national courts, the recognition and enforcement of judgments and the determination of the applicable law. The article highlights the implications of Brexit on the determination of the applicable law in the United Kingdom, more specifically, its impact on a tacit choice of law in international commercial contracts. The article examines the current legal position in the United Kingdom (i.e. the legal framework in a so-called “soft-Brexit” scenario). Secondly, the article analyses the effect of a complete withdrawal from the European Union (i.e. the legal framework in a “hard- Brexit” scenario).